Large-scale unconstrained optimization using separable cubic modeling and matrix-free subspace minimization - Brás, C. P. (2022)
PRONEX-CNPq/FAPERJ (E-26/111.449/2010-APQ1), CEPID-Industrial Mathematics/FAPESP (Grant 2011/51305-02), FAPESP (Projects 2013/05475-7 and 2013/07375-0). Fundacao para a Ciencia e a Tecnologia- project UID/MAT/00297/2019 (CMA).